Final answer:
To solve the equation 4 over 6(x + 4) = x over (x + 4) using common denominators, we can find a common denominator of (x + 4) and then solve the equation algebraically.
Step-by-step explanation:
To solve the equation, we need to find a common denominator. The common denominator in this case is (x + 4). We can rewrite the equation as:
4(x + 4) / 6(x + 4) = x / (x + 4)
Next, we can multiply both sides of the equation by 6(x + 4) to eliminate the denominators:
4(x + 4) = 6(x)
Expanding the equation gives:
4x + 16 = 6x
Move the terms with x to one side and the constant terms to the other side:
16 = 2x
Divide both sides of the equation by 2:
x = 8
Therefore, the solution to the equation is x = 8.